2016
DOI: 10.4310/cms.2016.v14.n8.a9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal transport for seismic full waveform inversion

Abstract: Abstract. Full waveform inversion is a successful procedure for determining properties of the earth from surface measurements in seismology. This inverse problem is solved by a PDE constrained optimization where unknown coefficients in a computed wavefield are adjusted to minimize the mismatch with the measured data. We propose using the Wasserstein metric, which is related to optimal transport, for measuring this mismatch. Several advantageous properties are proved with regards to convexity of the objective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
160
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(164 citation statements)
references
References 16 publications
0
160
0
Order By: Relevance
“…Our work is motivated in part by [7,8,34], where the authors use the quadratic Wasserstein metric to solve Full-Waveform Inversion (FWI) problems. In particular, it is demonstrated that the quadratic Wasserstein metric, as opposed to the L 2 norm, provides an effective measure of the misfit between given data and computed solution.…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Our work is motivated in part by [7,8,34], where the authors use the quadratic Wasserstein metric to solve Full-Waveform Inversion (FWI) problems. In particular, it is demonstrated that the quadratic Wasserstein metric, as opposed to the L 2 norm, provides an effective measure of the misfit between given data and computed solution.…”
Section: Prior Workmentioning
confidence: 99%
“…Our work extends that of [7,8,34] by considering different inverse problems, a more general noise model, and we use a different Wasserstein metric. See section 4.4 for more detail.…”
Section: Our Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the misfit between the synthetic and observed data is examined from another point of view, a mapping can be considered to exist between them (Ma & Hale, ; Engquist & Froese, ; Métivier et al, ; Yang et al, ). Recently, a novel measure of misfit related to optimal transport was proposed by Engquist and Froese ().…”
Section: Introductionmentioning
confidence: 99%